2018
DOI: 10.1007/s11250-018-1670-z
|View full text |Cite
|
Sign up to set email alerts
|

Direct and maternal variance components and genetic parameters for average daily body weight gain and Kleiber ratios in Nellore sheep

Abstract: The objective of the present study was to estimate variance components and genetic parameters for average daily gain from birth to weaning (ADGa), birth to 6 months (ADGb) and 3 to 6 months (ADGc) and corresponding Kleiber ratios (Ka, Kb, and Kc) in Nellore sheep. Data were collected from the records maintained at Livestock Research Station, Palamaner, for analysis and the data spread from 1993 to 2016 (23 years). Lambing year, sex of lamb, season of lambing, and parity of dam were included in the model as fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
0
2
1
Order By: Relevance
“…Likewise, the direct heritability estimate of PWDG (0.15) in the current study was in accordance with the estimated values reported by Mandal et al (2015), Jafari et al (2014) and Sallam et al (2019) in Muzaffarnagari, Makuie and Barki sheep, respectively. However, these results were incompatible with those obtained by Lalit et al (2016) in Harnali (0.40), Illa et al (2019) in Nellore (0.37) and Latifi and Mohammadi (2019) in Afhshari (0.37) sheep, who reported higher values. Other authors have also reported lower values for the mentioned trait compared to those estimated in the present study (Boujenane and Diallo 2017;Gholizadeh and Ghafouri-Kesbi 2017;Bangar et al 2018).…”
Section: Genetic Parameterscontrasting
confidence: 63%
See 1 more Smart Citation
“…Likewise, the direct heritability estimate of PWDG (0.15) in the current study was in accordance with the estimated values reported by Mandal et al (2015), Jafari et al (2014) and Sallam et al (2019) in Muzaffarnagari, Makuie and Barki sheep, respectively. However, these results were incompatible with those obtained by Lalit et al (2016) in Harnali (0.40), Illa et al (2019) in Nellore (0.37) and Latifi and Mohammadi (2019) in Afhshari (0.37) sheep, who reported higher values. Other authors have also reported lower values for the mentioned trait compared to those estimated in the present study (Boujenane and Diallo 2017;Gholizadeh and Ghafouri-Kesbi 2017;Bangar et al 2018).…”
Section: Genetic Parameterscontrasting
confidence: 63%
“…The moderate estimates of heritability for BW and WW in our study show that these traits have moderately heritable variation. Therefore, genetic gain in these traits may result from selection designs (Illa et al 2019).…”
Section: Genetic Parametersmentioning
confidence: 99%
“…In Nellore sheep, the genetic parameters and (co)variance components for body weight, average daily gain and Kleiber ratio's at different ages were estimated using animal model, direct genetic and maternal effects on the traits were evaluated, genetic diversity and effects of inbreeding on growth traits in Nellore sheep were also assessed in this sheep [10,11]. Rajkumar et al [12] studied the effect of management system (semi-intensive vs intensive) on the slaughter age with respect to carcass characteristics and other related traits.…”
Section: Introductionmentioning
confidence: 99%
“…In Nellore sheep, the genetic parameters and (co)variance components for body weight, average daily gain and Kleiber ratio's at different ages were estimated using animal model, direct genetic and maternal effects on the traits were evaluated, genetic diversity and effects of inbreeding on growth traits in Nellore sheep were also assessed in this sheep [10][11]. Raj kumar et al [12] studied the effect of management system (semi-intensive vs intensive) on the slaughter age with respect to carcass characteristics and other related traits.…”
Section: Introductionmentioning
confidence: 99%